Analisis Status Mutu Air Berbasis Indeks Pencemaran Pada Sungai Marengan Kecamatan Kota Sumenep - Ahmad Januarta Pratama; Ali, Munawar; Syadzadhiya Qothrunada Z.N (Jurnal Serambi Engineering, 2025)
The Marengan River serves as a critical freshwater resource for local residents; however, escalating human-induced activities have contributed to its declining water quality. This research aims to evaluate the river's water quality status through an analysis of water quality indicators and a pollution index assessment. The methodology included field observations, water sampling at five selected points along the river, and laboratory examinations measuring BOD, COD, TSS, DO, nitrate, phosphate, and total coliform levels. Findings revealed that BOD and COD concentrations at all locations surpassed the environmental quality standards, with the third sampling point exhibiting the most elevated levels. The calculated Pollution Index values ranged between 5.24 and 7.85, categorizing the river as moderately to heavily polluted. Key pollution contributors are presumed to include household wastewater, agricultural discharge, and organic matter. The study concludes that urgent action is needed to address the environmental degradation of the Marengan River, through wastewater treatment implementation, watershed area restoration, and active community participation. These interventions are recommended to foster sustainable river basin management and improve overall water quality.